Optimizing the discovery of predictors of vaso-occlusion in sickle-cell disease by proteomics - Lavinha, João (2012)
Painful crises are the major sickle-cell disease (SCD) clinical manifestation probably due to significant increase in dense red blood cells (RBC) and reduction of their ability to pass through capillaries. Using proteomic strategies (see figure below), we aimed to discover novel SCD prognosis biomarkers as early predictors of the transition from steady-state to vaso-occlusive crises thus, allowing a prompt and specific therapeutic intervention.